Underwater self-repairing fluorine-containing elastomer as well as preparation method and application thereof

By grafting pyridine groups on the fluoroelastic backbone and using dipole-dipole interaction, the underwater self-healing and mechanical properties of commercial fluoroelastomers are achieved, and the problems of unstable self-healing and insufficient mechanical properties in the prior art are solved, and are suitable for flexible electronic and energy devices.

CN119638875AActive Publication Date: 2025-03-18四川道弘新材料股份有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411928311.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve stable self-healing of polymers in humid environments, and there are few researches on self-healing of commercial fluorine-containing elastomers, making it difficult to maintain good mechanical properties.

Method used

By grafting pyridine groups on the main chain of the fluoroelastomer, dipole-dipole interactions of CF3-CF3 and CF3-pyridine N are used to achieve underwater self-healing of commercial fluoroelastomers, and the mechanical strength and dielectric properties of the material are enhanced through a simple chemical modification process.

Benefits of technology

It achieves excellent self-repair performance of fluorine-containing elastomers in air and water environments, maintains good mechanical strength, and significantly improves dielectric constant and piezoelectric properties, and is suitable for flexible electronic and energy devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638875A_ABST
    Figure CN119638875A_ABST
Patent Text Reader

Abstract

The invention provides an underwater self-repairing fluorine-containing elastomer as well as a preparation method and application thereof, and belongs to the field of high polymer materials. The fluorine-containing elastomer is obtained by grafting a pyridine group on a main chain of fluororubber. Self-repairing of the commercial fluorine-containing elastomer is achieved in a simple mode, and based on the dipole-dipole interaction of CF3-CF3 and CF3-pyridine N, the prepared fluorine-containing elastomer has excellent self-repairing performance (in air and water environments) and good mechanical strength; meanwhile, due to the introduction of pyridine polar groups, the dielectric constant of the material is greatly improved, and the material shows excellent piezoelectric property. The preparation process is simple, the obtained material has multiple functions and excellent comprehensive performance, and a new thought is provided for design and development of self-repairing elastomers for electronic and energy devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to an underwater self-repairing fluorine-containing elastomer and a preparation method and application thereof. Background Art

[0002] Polymers are widely used in various flexible electronic and energy devices, including energy harvesting and storage devices, wearable electronic devices, electronic skin, flexible sensors, flexible robots and flexible electronic circuits, due to their excellent mechanical properties. Although polymers used in flexible devices have the ability to adapt to large strains / stresses or geometric deformations, they are often subject to mechanical damage such as wear, tear, scratches and accidental cutting, as well as electrical damage under long-term strong electric fields during actual applications, which destroys the structural and functional integrity of the polymer part of the device, resulting in device performance degradation or even catastrophic failure. Therefore, giving polymer materials in flexible electronic and energy devices the ability to resist damage, wear and repair is of great significance to improving the stability and reliability of polymers in long-term use in flexible devices. Inspired by the powerful self-healing ability in biological systems, the concept of self-healing has been introduced into polymers to achieve self-repair of mechanical and electrical damage, thereby greatly improving the service life and reliability of flexible electronic and energy devices.

[0003] To achieve the "self-healing" ability of polymers, it is often necessary to introduce dynamic covalent bonds or supramolecular effects into the polymers to allow strong interactions between polymer chains, so that the broken surfaces can be reconnected. However, the self-healing polymers based on reversible dynamic covalent bonds or dynamic non-covalent bonds reported so far are usually unstable under humid conditions. In a humid environment, water molecules can play a variety of roles: donors and acceptors of hydrogen bonds, ligands, polar solvents, etc. This means that the dynamic bonds will be disturbed in many ways: water molecules will saturate hydrogen bonds, bind to metal cations, and solvate ions, thereby greatly reducing the bonding constants of these bonds, and the self-healing materials will gradually swell and lose their self-healing ability.

[0004] Ion-dipole interaction and dipole-dipole interaction are supramolecular interactions. Although the strength of the interaction force is far less than that of chemical bonds such as covalent bonds, they are commonly found between polymer chains. Some researchers have rationally used this supramolecular interaction to successfully design self-healing materials in complex environments, which are widely used in wearable devices and human-computer interaction interfaces. Although these methods use dipole-dipole and ion-dipole interactions to achieve the self-healing ability of materials under various aquatic conditions, the plasticizing effect of plasticizers or ionic liquids increases the distance between chains, resulting in generally weak mechanical properties of the materials.

[0005] The fluorine atom in fluorinated elastomer has a small atomic radius and the strongest electronegativity. The CF bond is a very poor hydrogen donor and hydrogen acceptor. The water environment makes the fluorinated polymer have a very weak acceptance of water molecules, which ensures the stability of the material underwater. Therefore, this characteristic of fluorinated elastomer can be used to develop water-resistant self-healing elastomers. Although there are reports on self-healing materials of fluorinated monomers, most of the polymer structures in these works are carefully designed, and their self-healing systems are "tailor-made". There are very few studies on the intrinsic self-healing of commercial fluorinated elastomers. How to achieve underwater self-healing of commercial fluorinated elastomers in a simple way and keep the fluorinated elastomers with good mechanical properties requires further research. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a fluorine-containing elastomer capable of underwater self-repairing, and a preparation method and use thereof.

[0007] The invention provides an underwater self-repairable fluorine-containing elastomer, wherein the fluorine-containing elastomer is obtained by grafting pyridine groups on the main chain of fluorine rubber.

[0008] Furthermore, the fluorine-containing elastomer is obtained by subjecting fluororubber to a dehydrogenation and defluorination reaction with an organic amine, followed by a Michael addition reaction with hydroxypyridine.

[0009] Further,

[0010] The mass volume ratio of the fluororubber to the organic amine is 10 g: (1-5) mL;

[0011] And / or, the temperature of the dehydrogenation and defluorination reaction is 10 to 40° C., and the reaction time is 10 to 20 hours;

[0012] And / or, the mass ratio of the fluororubber to hydroxypyridine is 10:(1-5);

[0013] And / or, the temperature of the Michael addition reaction is 10-40° C., and the reaction time is 10-20 hours.

[0014] Further,

[0015] The mass volume ratio of the fluororubber to the organic amine is 10 g:1.6 mL;

[0016] And / or, the mass ratio of the fluororubber to hydroxypyridine is 10:1.6.

[0017] Further,

[0018] The organic amine is triethylamine;

[0019] And / or, the hydroxypyridine is 3-hydroxypyridine.

[0020] The present invention also provides a method for preparing the aforementioned fluorine-containing elastomer, which comprises the following steps:

[0021] (1) In the solvent, fluororubber and organic amine undergo dehydrogenation and defluorination reactions;

[0022] (2) After the reaction in step (1) is completed, a hydroxypyridine solution is added to cause a Michael addition reaction to obtain the product.

[0023] Further,

[0024] In step (1), the solvent is a ketone or ester solvent;

[0025] And / or, in step (1), the mass volume ratio of the fluororubber to the organic amine is 10 g:(1-5) mL;

[0026] And / or, in step (1), the temperature of the dehydrogenation and defluorination reaction is 10 to 40° C., and the reaction time is 10 to 20 hours;

[0027] And / or, in step (2), the mass ratio of the fluororubber to hydroxypyridine is 10:(1-5);

[0028] And / or, in step (2), the solvent of the hydroxypyridine solution is a mixed solution of ethanol and ketones or esters;

[0029] And / or, in step (2), the temperature of the Michael addition reaction is 10 to 40° C., and the reaction time is 10 to 20 hours.

[0030] Further,

[0031] In step (1), the solvent is acetone;

[0032] And / or, in step (1), the mass volume ratio of the fluororubber to the organic amine is 10 g:1.6 mL;

[0033] And / or, in step (2), the mass ratio of the fluororubber to hydroxypyridine is 10:1.6;

[0034] And / or, in step (2), the solvent of the hydroxypyridine solution is a mixed solution of ethanol and acetone; preferably, the volume ratio of ethanol to acetone is 2:1;

[0035] And / or, in step (2), the product is washed and then dried after the reaction.

[0036] Further,

[0037] The organic amine is triethylamine;

[0038] And / or, the hydroxypyridine is 3-hydroxypyridine.

[0039] The present invention also provides the use of the aforementioned fluorine-containing elastomer in self-healing elastomers for electronic and energy devices;

[0040] Preferably, the fluorinated elastomer is used in preparing self-healing flexible electronic devices.

[0041] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0042] The present invention starts from the ionic cross-linking mechanism of fluororubber and completes the chemical modification of commercial fluororubber by a simple method. First, triethylamine is used to treat fluororubber (FKM) to generate a -CF=CH- double bond on the main chain, and then the hydroxyl group of 3-hydroxypyridine attacks the double bond, and the pyridine group is introduced into the main chain of the fluororubber, and a fluoroelastomer containing a pyridine group is successfully prepared. Based on the dipole-dipole interaction of CF3-CF3 and CF3-pyridine N, the prepared fluoroelastomer is not affected by water molecules and has excellent self-healing properties in both air and water environments; at the same time, the fluoroelastomer has good mechanical strength. And due to the introduction of the pyridine polar group, the dielectric constant of the fluoroelastomer is greatly improved, showing excellent dielectric and piezoelectric properties. The preparation process of the present invention is simple, and the obtained fluoroelastomer has multiple functionalities and excellent comprehensive performance. It has broad application prospects as a dielectric material in many flexible electronic and energy devices that require high stability, high reliability and good safety. The present invention provides a reference for using dipole forces to achieve self-healing of commercial materials.

[0043] In short, the present invention realizes the self-repair of commercial fluorinated elastomers in a simple way. Based on the dipole-dipole interaction of CF3-CF3 and CF3-pyridine N, the prepared fluorinated elastomer has excellent self-repairing performance (in air and water environments) and good mechanical strength; at the same time, due to the introduction of pyridine polar groups, the dielectric constant of the material is greatly improved, showing excellent piezoelectric properties. The preparation process of the present invention is simple, and the obtained materials have multiple functionalities and excellent comprehensive performance, which provides new ideas for the design and development of self-repairing elastomers for electronic and energy devices.

[0044] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0045] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The present invention is a flow chart for preparing the underwater self-repairable fluoroelastomer (FKM-HPY).

[0047] Figure 2 Infrared characterization spectra of different fluororubber samples: a is the infrared spectra of FKM and samples treated with triethylamine for different times; b is the infrared spectra of B-FKM-12H and FKM-HPY-2.

[0048] Figure 3 F1s spectra of B-FKM-12H and FKM-HPY-2.

[0049] Figure 4 A small molecule model for dipole-dipole interactions calculated using density functional theory (DFT).

[0050] Figure 5 The dipole-dipole interactions were calculated using all-atom molecular dynamics (MD) simulations of the polymer repeating units.

[0051] Figure 6 The stress-strain curves of B-FKM-12H and FKM-HPY-2.

[0052] Figure 7 These are the self-healing test results of FKM-HPY-2 in air: a is the stress-strain curve of 5 min repair at different repair temperatures in air, where Pristine is the initial sample; b is the stress-strain curve of different repair times at 40 °C in air; c is the stress-strain curve of 60 min self-healing at different temperatures in air.

[0053] Figure 8 Optical microscope image of a scratched FKM-HPY-2 film after healing at 60 °C.

[0054] Fig. 9 These are the self-healing test results of FKM-HPY-2 in water: a is the stress-strain curve of the original sample and the repaired sample in 20°C water at different times; b is the stress-strain curve of the self-healing sample in 60°C water for 60 minutes.

[0055] Fig.10The dielectric properties and conductivity results of various fluororubbers: a is the relationship between the dielectric constant and frequency of FKM, B-FKM-12H, FKM-HPY-1, and FKM-HPY-2 at 20°C; b is the conductivity of FKM at different temperatures (-40°C, -20°C, 0°C, 20°C, 40°C, and 60°C) as a function of frequency; c is the conductivity of B-FKM-12H at different temperatures as a function of frequency; d is the conductivity of FKM-HPY-2 at different temperatures as a function of frequency.

[0056] Fig.11 The output voltage and current results of FKM-HPY-2 under different conditions of applying 2n periodic external force: a is voltage; b is current. DETAILED DESCRIPTION

[0057] The raw materials and equipment used in the specific embodiments of the present invention are all known products and are obtained by purchasing commercially available products.

[0058] Commercial bisphenol-cured binary fluororubber (brand DH-7630) was purchased from Sichuan Daohong New Materials Co., Ltd. 3-Hydroxypyridine (Py, 98.0%) was purchased from Adamas Triethylamine, acetone, ethanol, and petroleum ether were purchased from Tansoole Company (China).

[0059] In the specific implementation manner of the present invention, the room temperature ranges from 20 to 30°C.

[0060] Example 1: Preparation of the underwater self-repairable fluoroelastomer (FKM-HPY) of the present invention

[0061] Preparation of polymer FKM-HPY (taking FKM-HPY-2 as an example): First, 10g of fluororubber was dissolved in 50ml of acetone in a 250ml beaker, and then 1.6ml of triethylamine was added dropwise. After reacting at room temperature for 12h, an ethanol-acetone solution (10ml of ethanol and 5ml of acetone) containing 3-hydroxypyridine (1.6g) was added, and the reaction was continued for 12h before the reaction was terminated. The obtained product was precipitated and washed three times in petroleum ether, and then washed three times with deionized water to remove unreacted monomers. It was dried in a vacuum oven at 60°C to constant weight to obtain a brown solid.

[0062] According to the preparation method of Example 1, FKM-HPY-1 was prepared by changing 3-hydroxypyridine from 1.6 g to 1 g.

[0063] Figure 1 The preparation process of the underwater self-healing fluorine-containing elastomer (FKM-HPY) of the present invention is as follows: first, fluororubber (FKM) is treated with triethylamine to generate a -CF=CH- double bond on the main chain, and then the hydroxyl group of 3-hydroxypyridine attacks the double bond to introduce the pyridine group into the fluororubber main chain.

[0064] Comparative Example 1: Preparation of other fluorinated elastomers (B-FKM)

[0065] Preparation of polymer B-FKM (taking B-FKM-12H as an example): First, dissolve 10g of fluororubber in 50ml of acetone in a 100ml beaker, then add 1.6ml of triethylamine dropwise, and continue to react at room temperature for 12h after the addition is complete. The obtained product is precipitated and washed three times in petroleum ether, and then washed three times with deionized water to remove unreacted monomers. Dry in a vacuum oven at 60°C to constant weight to obtain a yellow-brown solid. The 12H in B-FKM-12H refers to the reaction time of 12h.

[0066] According to the preparation method of Comparative Example 1, the reaction time was changed to 1h, 2h and 3h to prepare B-FKM-1H, B-FKM-2H and B-FKM-3H.

[0067] The beneficial effects of the present invention are demonstrated below through specific test examples.

[0068] Test Example 1: Structural Characterization of the Underwater Self-Healing Fluoroelastomer of the Present Invention

[0069] 1. Infrared spectroscopy characterization

[0070] The raw material fluororubber (FKM), FKM-HPY-2 prepared in Example 1, B-FKM-1H, B-FKM-2H, B-FKM-3H and B-FKM-12H prepared in Comparative Example 1 were characterized by infrared spectroscopy. The results are as follows: Figure 2 As shown. Figure 2 The infrared spectrum of a shows that the FTIR spectra of fluororubber treated with triethylamine for different time periods are compared with those of untreated fluororubber. -1 A stretching vibration peak corresponding to a non-conjugated double bond appeared at the position, and the peak gradually increased with the extension of the reaction time, which preliminarily proved that the fluororubber underwent a dehydrofluoric acid reaction in an alkaline environment and generated a double bond on the main chain. Figure 2 The infrared spectrum of b shows that at 1578cm -1 The vibration absorption peak corresponding to the ring deformation in the pyridine molecule plane appears at 1480cm -1 A vibration absorption peak corresponding to the CH deformation on the pyridine molecular skeleton appeared, proving that 3-hydroxypyridine was successfully connected to the fluororubber main chain.

[0071] 2. X-ray Photoelectron Spectroscopy (XPS) Characterization

[0072] The sample B-FKM-12H prepared in comparative example 1 and the sample FKM-HPY-2 prepared in example 1 were studied using the XSAM800 X-ray photoelectron spectrometer from Kratos, UK. The X-ray radiation source was Mg Ka (hv=253.ev), the test conditions were 12kV and 15mA, and the test mode was point acquisition. Narrow spectrum scanning was performed on C1s, N1s, O1s, and F1s, respectively.

[0073] In order to prove the existence of dipole interaction between CF3 dipole and pyridine N in 3-hydroxypyridine modified fluororubber, the present invention uses X-ray photoelectron spectroscopy (XPS) to study the position of 1s orbital binding energy peak of F before and after modification ( Figure 3 ).from Figure 3 It can be seen that the 1s binding energy peak of the modified (FKM-HPY-2)F shifted by 0.25 eV from 689 eV to 688.75 eV, indicating that there is an interaction between the electronegative CF3 group of the fluororubber side chain and the N cation on the pyridine ring.

[0074] 3. Small molecule model of dipole-dipole interaction

[0075] In order to further understand the dipole-dipole interaction between -CF3 and pyridine N, density functional theory calculations (DFT) and all-atom molecular dynamics simulations (All-atom MD simulations) were performed at the theoretical level. The results are as follows Figure 4 and Figure 5 As shown. Using a small molecule model, density functional theory (DFT) calculations show that the CF3-CF3 interaction energy is lower than the CF3-pyridine N interaction energy, proving the existence of dipole-dipole interaction between CF3 and pyridine N. The existence of dipole-dipole interaction in the polymer is further proved by all-atom molecular dynamics (MD) simulations. In order to save computing resources, 5 molecular chains with 12 repeating units were selected as polymer models for simulation calculations. The specific calculations were performed using the open source software Materials studio developed by Accelrys, USA. First, the amorphous polymer molecular chain was constructed using the Amphorous module; secondly, molecular dynamics calculations were performed using the Forcite module. The weak interaction energy of the entire polymer system was calculated by molecular dynamics, and the pyridine ring was compared with the benzene ring to further verify the dipole-dipole interaction between the polymers. During the simulation, the pyridine ring was replaced with the benzene ring, and the interaction energy was calculated. The energy was -363.053 kcal / mol, which was lower than that of the pyridine ring, indicating that there was a dipole-dipole interaction between CF3 and pyridine N.

[0076] Test Example 2: Mechanical properties test of the underwater self-repairable fluorinated elastomer of the present invention

[0077] The tensile test was conducted on an Instron 5967 tensile tester. The test samples (sample B-FKM-12H prepared in Comparative Example 1 and sample FKM-HPY-2 prepared in Example 1) were dumbbell-shaped, with an inner gauge length of 20 mm, a width of 2 mm, and a thickness of 1 mm, and the test rate was 100 mm / min.

[0078] The dipole-dipole interaction between -CF3 and pyridinic N and its effect on the mechanical properties of fluorinated elastomers were studied by uniaxial tensile tests. Figure 6 It can be seen that the dipole interaction between -CF3 and pyridine N has a certain contribution to the tensile strength. The tensile strength of FKM-HPY-2 reaches about 1MPa, which is significantly better than the fluoroelastomer without pyridine.

[0079] Test Example 3: Self-repairing performance test of the underwater self-repairing fluoroelastomer of the present invention

[0080] The sample self-healing efficiency is defined as the ratio of the tensile strength of the repaired sample to the tensile strength of the original sample, as shown in the following formula (1):

[0081]

[0082] where σ cut represents the tensile strength of the repaired specimen after cutting, σ uncut Represents the tensile strength of the original sample. The tensile rate is 100 mm / min.

[0083] The present invention uses FKM-HPY-2 prepared in Example 1 to study the self-healing properties of pyridine-grafted fluorine-containing elastomer. Uniaxial tensile tests were performed on the original and repaired specimens. First, the complete original specimen was cut into two halves, and then gently spliced ​​together. Without applying external force, the specimen was allowed to repair in different environments, different temperatures, and different times.

[0084] Figure 7 a shows the self-healing ability of FKM-HPY-2 in air at different temperatures. It can be seen that the self-healing speed of fluorinated elastomer in air is very fast. At 20°C, 97.6% of its original tensile strength can be restored in 5 minutes, but the strain repair efficiency is relatively low. After 5 minutes of repair at 20°C, the strain is 3.8% of the original strain. Figure 7b and 7c show that increasing the repair temperature or extending the repair time has a positive effect on the strain repair efficiency of the polymer. For example, when the repair temperature rises to 40°C, the strain is 1300% after 60 minutes of repair and 2000% after 120 minutes of repair (the original strain is 1940%). On the one hand, increasing the temperature can improve the mobility of the polymer segments, thereby promoting the dynamics of the dipole-dipole interaction; on the other hand, extending the repair time provides favorable conditions for the migration and diffusion of the polymer segments in the damaged interface area. These two factors synergistically promote the self-repair process.

[0085] The self-healing process of the sample (FKM-HPY-2) was visually observed by polarizing microscope. First, a scratch of about 30 to 50 μm was pre-made on the sample film with a single-sided blade, and then it was placed on a polarizing microscope hot stage (preset temperature 60°C) to observe the scratch repair process. Figure 8 It can be seen that the scratch gradually began to close within 30 seconds and almost completely disappeared within 90 seconds.

[0086] The results of the sample (FKM-HPY-2) repaired at 20℃ water temperature for different time periods are as follows Fig. 9 As shown in a, after 30 minutes of underwater repair, the tensile strength of the sample can reach 96% of the original tensile strength of the sample. As the time is extended to 60 minutes, the strain reaches 115%, which means that the material of the present invention can indeed self-repair underwater. On this basis, the present invention tested the self-repairing performance of the sample in 60°C water, and the results are as follows Fig. 9 As shown in Figure b, after 60 minutes of self-healing, the tensile strength of the sample recovered to about 95% of the original strength, while the strain was almost completely recovered. These results indicate that the hydrophobic nature of the fluororubber main chain eliminates the interference of water molecules and ensures that the dipole-dipole interaction between the polymer interior and the contact surface is still effective underwater.

[0087] Test Example 4: Electrical performance test of the underwater self-repairable fluoroelastomer of the present invention

[0088] The raw material fluororubber (FKM), FKM-HPY-1 and FKM-HPY-2 prepared in Example 1, and B-FKM-12H samples prepared in Comparative Example 1 were tested.

[0089] The broadband dielectric test of the samples was carried out on a Nococontrol Concept 50 system equipped with an Alpha impedance analyzer and a Quatro Cryosystem temperature controller. Test method: A disc-shaped sample with a thickness of about 1 mm and a diameter of 20 mm was placed between two parallel copper electrodes, clamped and placed in the test instrument. The frequency range of the variable temperature sweep mode was 10 -1 ~10 7Hz, temperature range is -60℃~60℃, and temperature gradient is 10℃.

[0090] Piezoelectric performance test: Aluminum foil was pasted on both sides of the sample and corona polarization was performed for 60 minutes using a piezoelectric material composite polarizer (Shaanxi Huiyan New Material Technology Co., Ltd., HYJH-F) at a temperature of 100°C and a voltage of 20 kV / mm. The polarized sample was then coated with aluminum tape as an electrode and wire and wrapped with a polyimide film. A linear motor (NTIAG, USA, HS01-37166), an electrometer (Keithley Instruments, USA, 6514) and a current preamplifier (SRS, USA, SR570) were used to test the piezoelectric output performance of the sample, and the impact force was about 2N.

[0091] The introduction of pyridine groups increases the dielectric constant of fluororubber. For example, at room temperature 20°C and frequency 100Hz, the dielectric constant of FKM-HPY-2 reaches 22.5, which is more than twice the dielectric constant of conventional fluororubber ( Fig.10 a) The conductivity results of FKM, B-FKM-12H, and FKM-HPY-2 are as follows Fig.10 b, 10c and 10d. It can be seen that due to the presence of carbon-carbon double bonds on the main chain, the electron delocalization of the fluororubber and pyridine-grafted fluoroelastomer treated with triethylamine is enhanced, and the charge migration and accumulation process is more obvious, thereby increasing the conductivity.

[0092] The piezoelectric response of FKM-HPY-2 was further investigated. Fig.11 The output open circuit voltage and short circuit current of FKM-HPY-2 under different conditions (the original sample just prepared, the sample stored in air for 7 days, the self-repaired sample after self-repairing at 40℃ for 60 minutes, and the sample stored in air for 7 days after self-repair) are shown. Fig.11 It can be seen that the FKM-HPY-2 before and after repair has a stable continuous piezoelectric response to cyclic load. The undamaged FKM-HPY-2 shows a better piezoelectric response, with an output voltage stable at around 32V and a short-circuit current of 0.9μA; the output voltage and short-circuit current of the repaired sample decreased slightly, but the voltage remained at around 29V and the short-circuit current was 0.5μA, indicating that the damaged piezoelectric network structure has been completely restored.

[0093] In summary, the present invention successfully prepares a fluorine-containing elastomer containing pyridine groups, and realizes the self-healing of commercial fluorine-containing elastomers. Based on the dipole-dipole interaction of CF3-CF3 and CF3-pyridine N, the prepared fluorine-containing elastomer has excellent self-healing properties in both air and water environments; at the same time, the fluorine-containing elastomer has good mechanical strength. And due to the introduction of pyridine polar groups, the dielectric constant of the fluorine-containing elastomer is greatly improved, showing excellent dielectric and piezoelectric properties. The preparation process of the present invention is simple, and the obtained fluorine-containing elastomer has multiple functionalities and excellent comprehensive performance. It has broad application prospects as a dielectric material in many flexible electronic and energy devices that require high stability, high reliability and good safety. The present invention provides a reference for the use of dipole forces to achieve self-healing of commercial materials.

Claims

1. A fluorinated elastomer capable of underwater self-repairing, characterized in that: The fluorine-containing elastomer is obtained by grafting pyridine groups onto the main chain of fluorine rubber.

2. The fluorinated elastomer according to claim 1, characterized in that: The fluorine-containing elastomer is obtained by subjecting fluorine rubber and organic amine to dehydrogenation and defluorination reactions, followed by Michael addition reaction with hydroxypyridine.

3. The fluorine-containing elastomer according to claim 2, characterized in that: The mass volume ratio of the fluororubber to the organic amine is 10 g: (1-5) mL; And / or, the temperature of the dehydrogenation and defluorination reaction is 10 to 40° C., and the reaction time is 10 to 20 hours; And / or, the mass ratio of the fluororubber to hydroxypyridine is 10:(1-5); And / or, the temperature of the Michael addition reaction is 10-40° C., and the reaction time is 10-20 hours.

4. The fluorine-containing elastomer according to claim 2, characterized in that: The mass volume ratio of the fluororubber to the organic amine is 10 g:1.6 mL; And / or, the mass ratio of the fluororubber to hydroxypyridine is 10:1.

6.

5. The fluorine-containing elastomer according to any one of claims 1 to 4, characterized in that: The organic amine is triethylamine; And / or, the hydroxypyridine is 3-hydroxypyridine.

6. The method for preparing a fluorine-containing elastomer according to any one of claims 1 to 5, characterized in that: It includes the following steps: (1) In the solvent, fluororubber and organic amine undergo dehydrogenation and defluorination reactions; (2) After the reaction in step (1) is completed, a hydroxypyridine solution is added to cause a Michael addition reaction to obtain the product.

7. The preparation method according to claim 6, characterized in that: In step (1), the solvent is a ketone or ester solvent; And / or, in step (1), the mass volume ratio of the fluororubber to the organic amine is 10 g:(1-5) mL; And / or, in step (1), the temperature of the dehydrogenation and defluorination reaction is 10 to 40° C., and the reaction time is 10 to 20 hours; And / or, in step (2), the mass ratio of the fluororubber to hydroxypyridine is 10:(1-5); And / or, in step (2), the solvent of the hydroxypyridine solution is a mixed solution of ethanol and ketones or esters; And / or, in step (2), the temperature of the Michael addition reaction is 10 to 40° C., and the reaction time is 10 to 20 hours.

8. The preparation method according to claim 7, characterized in that: In step (1), the solvent is acetone; And / or, in step (1), the mass volume ratio of the fluororubber to the organic amine is 10 g:1.6 mL; And / or, in step (2), the mass ratio of the fluororubber to hydroxypyridine is 10:1.6; And / or, in step (2), the solvent of the hydroxypyridine solution is a mixed solution of ethanol and acetone; preferably, the volume ratio of ethanol to acetone is 2:1; And / or, in step (2), the product is washed and then dried after the reaction.

9. The preparation method according to claim 8, characterized in that: The organic amine is triethylamine; And / or, the hydroxypyridine is 3-hydroxypyridine.

10. Use of the fluorinated elastomer according to any one of claims 1 to 4 in self-healing elastomers for electronic and energy devices; Preferably, the fluorinated elastomer is used in preparing self-healing flexible electronic devices.

Citation Information

Patent Citations

  • Grafted fluoroelastomers

    CN101001889A

  • Graft copolymers of a poly(vinylidene fluoride)-based polymer and at least one type of electrically conductive polymer, and methods for forming the graft copolymers

    CN104053689A

  • Metal coordination bond and hydrogen bond hybrid crosslinked self-repairing silicon elastomer, and preparation method thereof

    CN109422880A

  • Fluorochlorine elastomer material with multiple excellent properties and preparation method thereof

    CN110628143A

  • A dielectric material

    CN112292422A